Сlinical and laboratory features of Reye's syndrome in children: a clinical case - O.K. Koloskova; R.V. Tkachuk; T.M. Bilous; L.V. Kolyubakina; N.K. Bogutska (Zaslavsky O.Yu., 2021)
Reye's syndrome is a very rare disease that occurs in the pediatric population with a frequency of approximately 6 cases per 100,000 children, but the mortality due to this nosology is quite high and depends on its severity and prognostic factors. This pathology should be a warning for practitioners in terms of diagnosis and timely precautions for possible progression of the disease, taking into account the high mortality rate, the rapid progression of neurological symptoms, and lack of clear predictors of Reye's syndrome. The article presents modern views on the etiology, pathogenesis, clinical course, laboratory and morphological diagnosis of Reye's syndrome. Recommended by the Center for Disease Control and Prevention in Atlanta criteria for the diagnosis of Reye's syndrome are given in the article. The article describes the differential diagnosis between classical (aspirin-associated, idiopathic) and atypical Reye's syndrome (Reye's-like syndrome), as well as focuses on a set of diagnostic and therapeutic measures. A clinical case of the classic Reye's syndrome in pediatric practice is presented, which occurred in the Regional Municipal Non-Profit Enterprise "Chernivtsi Regional Children's Clinical Hospital". The presented clinical case, unfortunately, was fatal and the body was subjected to an autopsy, the results of which, as well as morphological changes in the section material after specific staining with Sudan III, are also described in the article. The review of the case ends with a summary and conclusions, authors emphasize the need to draw the attention of practitioners to the possibility of developing rare Reye's syndrome in children after the use of acetylsalicylic-containing drugs; for the verification of nosology, a doctor should take into account specific changes in clinical and paraclinical parameters, and due to the absence of a minimum permitted dose of acetylsalicylic acid it should be prohibited for use in pediatric practice as an antipyretic drug.